1915
DOI: 10.1136/bmj.2.2852.318
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Certain Antiseptic Substances in the Treatment of Infected Wounds

Abstract: IN order to make a jucdicious clhoice of the antiseptic most likely to give useful results in the treatment of infected wounds m:lany different factors lhave to be considered in addition to germicidal activity, including tlle irritating properties of the substances, their toxicity, solubility, ability to penetrate tissues and to be absorbed, and their chemical reactions with proteins and other tissue constituents.The k.illing of bacteria by ordinary antiseptic substances is esseiltially a clhemiical reaction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
15

Year Published

1919
1919
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(78 citation statements)
references
References 0 publications
0
63
0
15
Order By: Relevance
“…Dakin noted that sodium hypochloride was a very effective germicide but irritating to skin. He found adding boric acid neutralised the solution, making it effective but also non-irritating [20]. In another trial A. Carrel found that the antiseptic action of Dakin's hypochlorite solution was short-lived so had to be renewed frequently [21].…”
Section: Wound Infectionmentioning
confidence: 99%
“…Dakin noted that sodium hypochloride was a very effective germicide but irritating to skin. He found adding boric acid neutralised the solution, making it effective but also non-irritating [20]. In another trial A. Carrel found that the antiseptic action of Dakin's hypochlorite solution was short-lived so had to be renewed frequently [21].…”
Section: Wound Infectionmentioning
confidence: 99%
“…During World War I, the chemist Henry Drysdale Dakin and the surgeon Alexis Carrel used buffered 0.5% NaOCl to wash and disinfect infected wounds, based on Dakin's study of the effectiveness of different solutions on infected necrotic tissues (5,6). …”
Section: Sodium Hypochlorite (Naocl)mentioning
confidence: 99%
“…Based on the controlled laboratory studies by Koch and Pasteur, hypochlorite then gained wide acceptance as a disinfectant by the end of the 19 th century. In World War I, the chemist Henry Drysdale Dakin and the surgeon Alexis Carrel extended the use of a buffered 0.5% sodium hypochlorite solution to the irrigation of infected wounds, based on Dakin meticulous studies on the efficacy of different solutions on infected necrotic tissue (Dakin, 1915). Besides their wide-spectrum, nonspecific killing efficacy on all microbes, hypochlorite preparations are sporocidal, virucidal , and show far greater tissue dissolving effect on necrotic than on vital tissues ( Austin & Taylor, 1918) .…”
Section: Sodium Hypochloritementioning
confidence: 99%